2020
DOI: 10.1093/gbe/evaa242
|View full text |Cite
|
Sign up to set email alerts
|

The Origin and Evolution of Antistasin-like Proteins in Leeches (Hirudinida, Clitellata)

Abstract: Bloodfeeding is employed by many parasitic animals and requires specific innovations for efficient feeding. Some of these innovations are molecular features that are related to the inhibition of hemostasis. For example, bloodfeeding insects, bats and leeches release proteins with anticoagulatory activity through their salivary secretions. The antistasin-like protein family, composed of serine protease inhibitors with one or more antistasin-like domains, is tightly linked to inhibition of hemostasis in leeches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…These proteins have been reported to mediate several biological functions associated with envenomation including platelet aggregation and inflammation, as well as mitogenic, chemotactic, and cytotoxic activities ( Edo et al 2012 ; Sartim and Sampaio 2015 ). We also identified putative predatory toxins with antistasin-like domains ( table 1 , supplementary file S4, Supplementary Material online), which are common anticoagulants in leech saliva and have been also recorded from other nonblood-feeding invertebrates such as cnidarians and mollusks where they may act as modulators of the immune response ( Iwama et al 2021 ). To provide more evidence about the toxic nature and potential predatory role of these putative toxins, we looked at their spatial distribution within the A. valida proboscis tissue by MALDI-IMS.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins have been reported to mediate several biological functions associated with envenomation including platelet aggregation and inflammation, as well as mitogenic, chemotactic, and cytotoxic activities ( Edo et al 2012 ; Sartim and Sampaio 2015 ). We also identified putative predatory toxins with antistasin-like domains ( table 1 , supplementary file S4, Supplementary Material online), which are common anticoagulants in leech saliva and have been also recorded from other nonblood-feeding invertebrates such as cnidarians and mollusks where they may act as modulators of the immune response ( Iwama et al 2021 ). To provide more evidence about the toxic nature and potential predatory role of these putative toxins, we looked at their spatial distribution within the A. valida proboscis tissue by MALDI-IMS.…”
Section: Resultsmentioning
confidence: 99%
“…, no anticoagulant motifs (obtained from Iwama et al 2021) were found on the Antistasin sequences. In non-blood-feeding invertebrates, antistasin and proteins with similar domains are thought to have a role in immune responses, though their role remains unclear (Iwama et al 2021).…”
Section: )mentioning
confidence: 94%
“…, no anticoagulant motifs (obtained from Iwama et al 2021) were found on the Antistasin sequences. In non-blood-feeding invertebrates, antistasin and proteins with similar domains are thought to have a role in immune responses, though their role remains unclear (Iwama et al 2021). Verdes et al (2022) found antistasin in the proboscis of the hoplonemertean Antarctonemertes valida, in which it likely is a predation toxin.…”
Section: )mentioning
confidence: 94%
“…Even more proteins have been assayed for their functionality. Protein functionality is often as distinctive as morphology, such as for leech anticoagulants that are often highly distinctive for species or lineages (Iwama et al, 2021(Iwama et al, , 2022.…”
Section: Moving Forward a Proposalmentioning
confidence: 99%